KETERKAITAN PERTUMBUHAN EKONOMI DAN PENDAPATAN PERKAPITA TERHADAP KEMISKINAN PROVINSI JAWA TENGAH TAHUN 2003-2010 - Ayula Candra; Benediktus Riandoko; Dita Yuniar Saskia (MEDIA, 2012)
One of Millenium Development Goals is toÂ reduce the poverty. Central Java became one of province in Java Island which has the highest percentage of the average of poor inhabitant. Economic growth in Central Java is not always followed with reducing the amount of poor inhabitant. The increasing of population in Central Java is not always followed by the increasing of poor inhabitant. Based on that condition, the aims of this research are to analize the influence of economic growth, and percapita income towards poverty in Central Java. We uses fixed effect model to analyse this research. The result is economic growth and percapita income negatively and significantly affects poverty in Central Java in 2003 till 2010.